Multifunctional biomaterial platforms for blocking the fibrosis process and promoting cellular restoring effects in myocardial fibrosis therapy - Yue, Tian; Xiong, Shiqiang; Zheng, Dezhi; Wang, Yi; Long, Pan; Yang, Jiali; Danzeng, Dunzhu; Gao, Han; Wen, Xudong; Li, Xin; Hou, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Myocardial fibrosis is the result of abnormal healing after acute and chronic myocardial damage and is a direct cause of heart failure and cardiac insufficiency. The clinical approach is to preserve cardiac function and inhibit fibrosis through surgery aimed at dredging blood vessels. However, this strategy does not adequately address the deterioration of fibrosis and cardiac function recovery. Therefore, numerous biomaterial platforms have been developed to address the above issues. In this review, we summarize the existing biomaterial delivery and restoring platforms, In addition, we also clarifythe therapeutic strategies based on biomaterial platforms, including general strategies to block the fibrosis process and new strategies to promote cellular restoring effects. The development of structures with the ability to block further fibrosis progression as well as to promote cardiomyocytes viability should be the main research interests in myocardial fibrosis, and the reestablishment of structures necessary for normal cardiac function is central to the treatment of myocardial fibrosis . Finally, the future application of biomaterials for myocardial fibrosis is also highlighted.